Leaching of rare earth elements from bastnasite ore (third part) - Stopić, Srećko R.; Friedrich, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2019)
Sulfuric acid dissolution of rare earth elements from bastnasite ore was studied after reductive smelting with carbon as a reducing agent at 1600°C. The two-step strategy: 1.carbothermic reduction, and 2.dissolution with sulfuric acid at 70°C was applied under atmospheric pressure aiming at an increased selective extraction of rare earth elements from slag containing rare earth elements.